2018
DOI: 10.1159/000490225
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genes Involved in Persistent Atrial Fibrillation: Comparisons of ‘Trigger’ and ‘Substrate’ Differences

Abstract: Background/Aims: Recent research has improved our understanding of the pulmonary vein and surrounding left atrial (LA-PV) junction and the left atrial appendage (LAA), which are considered the ‘trigger’ and ‘substrate’ in the development of atrial fibrillation (AF), respectively. Herein, with the aim of identifying the underlying potential genetic mechanisms, we compared differences in gene expression between LA-PV junction and LAA specimens via bioinformatic analysis. Methods: Microarray data of AF (GSE41177)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Weighted gene co-expression network analysis has been applied to identify the core genes in AF. For example, Zou et al (2018) reported that LEP, FOS, EDN1, NMU, CALB2, TAC1 may be related to the occurrence and maintenance of AF using WGCNA method and public dataset GSE41177. Li et al (2020) used GSE79768 to perform a WGCNA analysis to determine the key modules related to atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Weighted gene co-expression network analysis has been applied to identify the core genes in AF. For example, Zou et al (2018) reported that LEP, FOS, EDN1, NMU, CALB2, TAC1 may be related to the occurrence and maintenance of AF using WGCNA method and public dataset GSE41177. Li et al (2020) used GSE79768 to perform a WGCNA analysis to determine the key modules related to atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when we directly compared WT and TNF-KO swim atria, the majority of genes were increased in exercised atria from TNF-KO relative to WT, with the only gene that was increased in a TNF-dependent manner after 2 weeks of exercise in WT atria was Comp, which is a biomarker for cardiac fibrosis and hypertrophic remodeling (Huang et al, 2013;Zhao et al, 2018). Comp is involved in noncollagen ECM-receptor interaction (Rosenberg et al, 1998) and appears from multiple studies to contribute to the pathogenesis of AF (Zou et al, 2018;Thomas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth stating that many specific ECM/mechanosensing-related genes whose expression was downregulated in TNF-dependent manner with exercise have been linked previously to AF and ECM remodeling, including Comp (Zou et al, 2018;Thomas et al, 2019), Thbs2 (Yang et al, 2000), Ltbp1 and Fbn1 (Zhang et al, 2020; Figure 3 and Table 1). On the other hand, most genes linked to collagen production (i.e., Col1a1, Col1a2, Col3a1) were TNF-independent.…”
Section: Transcriptional Responses In Atria After 2 Weeks Of Exercisementioning
confidence: 91%
“…A study including patients with persistent AF, who underwent LA tissue characterization with MRI scans and concomitant high-density mapping of the LA, demonstrated increased AF rotor activity in areas of relatively low and patchy late-gadolinium enhancement (LGE) [ 42 ]. Bioinformatics’ analysis has recently revealed that LA–PV junction demonstrates distinct gene expression differences in AF patients as compared to sinus rhythm (SR) controls, favoring extracellular matrix (ECM) synthesis and chemokine up-regulation [ 43 ].…”
Section: Atrial Fibrillation Pathogenesismentioning
confidence: 99%